Late complex tensile fracturing interacts with topography at Cumbre Vieja, La Palma - Walter, Thomas R.; Zorn, Edgar U.; González, Pablo J.; Sansosti, Eugenio; Muñoz, Valeria; Shevchenko, Alina V.; Plank, Simon Manuel; Reale, Diego; Richter, Nicole (Volcanica, 2023)
Volcanic eruptions are often preceded by episodes of inflation and emplacement of magma along tensile fractures. Here we study the 2021 Tajogaite-Cumbre Vieja eruption on La Palma, Canary Islands, and present evidence for tensile fractures dissecting the new cone during the terminal stage of the eruption. We use synthetic aperture radar (SAR) observations, together with drone images and time-lapse camera data, to determine the timing, scale and complexities associated with a fracturing event, which is diverging at a topographic ridge. By comparing the field dataset with analogue models, we further explore the details of lens-shaped fractures that are characteristic for faults diverging at topographic highs and converging at topographic lows. The observations made at Cumbre Vieja and in our models are transferrable to other volcanoes and add further evidence that topography is substantially affecting the geometry and complexity of fractures and magma pathways, and the locations of eruptions.